APPLICATION OF SERVICE QUALITY METHOD TO PUBLIC HEALTH CENTER PATIENT - Nency Widya Monalisa; William Ramdhan; Elly Rahayu (STMIK Royal, 2023)
Abstract: Providing services to patients is an obligation that must be carried out by health agencies. Of course, good health services can be measured by the performance of medical personnel. The current problem with the Aek Loba Health Center is that it does not have a system that can measure the level of patient satisfaction with the services provided. In addition, patients also still have difficulty in expressing opinions in the form of complaints about the performance of medical personnel. The aim of the research is to become a forum for assessing the quality of service that can make it easier for patients to submit complaints and also as a measuring tool for health agencies on the level of success of the quality of services provided. This study uses the Service Quality method by assessing service quality based on 5 quality dimensions, namely Tangibles, Responsiveness, Reliability, Assurance, and Empathy. Based on these problems, a decision support system was designed using the PHP programming language and the database used, namely MySQL. So that this research resulted in this system being able to help and facilitate the Aek Loba Health Center in accommodating and measuring the level of quality of service to patients. In addition, this system can make it easy for leaders to find out the elements that need to be improved, maintained, and repaired by the Aek Loba Health Center. Keywords: patient; questionaire; service quality Abstrak: Memberi pelayanan kepada pasien merupakan kewajiban yang harus dilakukan oleh instansi kesehatan. Pelayanan kesehatan yang baik tentu saja dapat diukur dari kinerja tenaga medisnya. Permasalahan Puskesmas Aek Loba saat ini yaitu belum mempunyai sistem yang dapat mengukur tingkat kepuasan pasien terhadap layanan yang diberikan. Selain itu, pasien juga masih kesulitan dalam menyampaikan pendapat berupa keluhan terhadap kinerja tenaga medis. Tujuan penelitian untuk menjadi wadah penilaian kualitas pelayanan yang dapat memudahkan pasien dalam menyampaikan keluhan dan juga sebagai alat ukur instansi kesehatan terhadap tingkat keberhasilan kualitas pelayanan yang diberikan. Penelitian ini menggunakan metode Service Quality dengan menilai kualitas pelayanan berdasarkan 5 dimensi kualitas, yaitu Bukti Nyata (tangibles), Ketanggapan (responsiveness), Kehandalan (reliability), Jaminan (assurance), dan Empati (emphaty). Berdasarkan permasalah tersebut maka dirancang sebuah sistem pendukung keputusan menggunakan bahasa pemrograman PHP dan database yang digunakan yaitu MySQL. Sehingga penelitian ini menghasilkan sistem ini dapat membantu dan mempermudah pihak Puskesmas Aek Loba dalam menampung dan mengukur tingkat kualitas pelayanan terhadap pasien. Selain itu, sistem ini dapat memberi kemudahan bagi pimpinan untuk mengetahui unsur-unsur yang perlu ditingkatkan, dipertahankan, serta diperbaiki oleh Puskesmas Aek Loba. Kata kunci: kuesioner; pasien; service quality